Pyrolysis behaviour and synergistic effect in co-pyrolysis of wheat straw and polyethylene terephthalate: A study on product distribution and oil characterization - Anis Kumar M; Swarnalatha A.P; Shwetha J; Sowmya Dhanalakshmi C; Saravanan P; Ashraf Atef Hatamleh; Munirah Abdullah Al-Dosary; Ravishankar Ram Mani; Woo Jin Chung; Soon Woong Chang; Balasubramani Ravindran (Heliyon, 2024)
Renewable lignocellulosic biomass is a favorable energy resource since its co-pyrolysis with hydrogen-rich plastics can produce high-yield and high-quality biofuel. In contrast to earlier co-pyrolysis research that concentrated on increasing product yield, this study comprehends the synergistic effects of two distinct feedstocks that were not considered earlier. This work focuses on co-pyrolyzing wheat straw (WS) with non-reusable polyethylene terephthalate (PET) for the production of pyrolysis oil. WS and PET were blended in different ratios (100/0, 80/20, 60/40, 40/60, 20/80, and 0/100), and pyrolysis experiments were conducted in a fixed-bed reactor under different temperatures to assess their synergistic effect on oil yield. Synergy rates of up to 7.78 % were achieved on yield for the blends of plastic and biomass at a temperature of 500 °C. In comparison to individual biomass or plastics, co-pyrolyzing PET-biomass blends demonstrated good process interaction and promoted the yields of value-added products. The heating value of the pyrolysis oils was in the range of 16.45–28.64 MJ/kg, which depends on the amount of plastic present in the feedstock. The physical analysis of the oils shows that they can be used for heat production by direct combustion in boilers or furnaces. The correlation between WS and PET was validated with the aid of Fourier transform infrared spectroscopy (FT-IR) and gas chromatography-mass spectrometry (GC-MS) analysis. The GC-MS result demonstrated the presence of different compounds such as O-H compounds, esters, carbonyl group elements, acids, hydrocarbons, aromatics, and nitrogenated compounds in the pyrolysis oil, which differed based on the proportions of PET in the feedstock. The increased hydrocarbon and reduced oxygen percentages in the pyrolysis oil were implicitly caused by enhanced hydrocarbon pool mechanisms, in which the breakdown of PET may be supplied as a hydrogen donor. Overall, waste lignocellulosic biomass and plastics can be used to produce biofuels, which helps reduce the amount of solid waste that ends up in landfills. This study also revealed that future research should be focused on the reaction mechanisms of WS and PET co-pyrolysis in order to examine the synergistic interactions.